Moral relativism as a disconnect between behavioural and experienced warm glow - Ferguson, Eamonn; Flynn, Niall (Elsevier, 2016)
We examine the robustness of warm glow preferences to changes in the choice set. Behavioural warm glow is measured using the crowded-out charity dictator game of Crumpler and Grossman (2008). In the give treatment, subjects could donate any part of their endowment to charity where their donations completely crowd out the charity's own initial endowment. In the give/take treatment, the option to take any part of the charity's endowment was added to the subjects' choice set. Experienced warm glow is measured by a series of post-decision self-reports of positive affect. Within each treatment behavioural and experienced warm glow are positively correlated, such that the more subjects donated to charity the better they claimed to feel about themselves. However, when comparing across treatments the addition of the take option results in a fall in behavioural warm glow but a rise in experienced warm glow. We interpret these results as evidence for i) a utility function increasing in both money and morality and ii) a type of moral relativism whereby the morally good action is defined in relation to the available options. This means that utility is derived from both the chosen option and from foregone opportunities, the implication of which is that the transitivity axiom becomes practically unfalsifiable.